Pengaruh Promosi Penjualan Terhadap Keputusan Pembelian Dengan Citra Merek Sebagai Variabel Intervening - Efi Pertiwi Rahayu; Esti Dwi Rahmawati; Rayhan Gunaningrat (Jurnal Bisnis Manajemen dan Akuntansi (BISMAK), 2025)
This study aims to analyze the effect of Sales Promotion on Emina Product Purchase Decisions with Brand Image as an Intervening Variable (Case Study of Emina Product Users in Karanganyar Regency). The population in this study were Emina users in Karanganyar Regency with a sample of 100 respondents. Non-probability sampling technique with a sampling technique using purposive sampling and the target respondents who have purchased Emina products. The research method used in this study is a quantitative method. The data used are primary data and secondary data. The data collection method used was a questionnaire in the form of a google form. The data analysis technique used was Partial Least Square (PLS). The results of this study indicate that the original sample value is 0.196 (positive) with a t-value of 2.333 > t-table (1.96) and a p-value of 0.022 <0.05, meaning that sales promotion has a positive and significant effect on purchasing decisions, the value of the original sample of 0.506 (positive) with a calculated t value of 5.870 > t table (1.96) and a p-value of 0.000 <0.05 meaning that sales promotion has a positive and significant effect on brand image, the original sample value is 0.634 (positive) with a t value count of 9,534 > t table (1.96) and p-value 0,000 <0.05 means that brand image has a positive and significant effect on purchasing decisions, the original sample value is 0,323 (positive) with a calculated t value of 4,319 > t table (1 .96) and a p-value of 0.000 <0.05 promotion has a positive effect on purchasing decisions through brand image.